Digital skills in the workplace and training of jobseekers and employees - Minčičová, Monika (Technium Social Sciences Journal, 2020)
At least some level of digital skills is becoming a prerequisite for practicing almost any profession. It is more than likely that in the future, the requirements of having command of technologies of various types and complexities will only increase. The starting point of sustainable employment and that of the upcoming generation entering the workforce is a transformation of education systems into a form adapted to the current requirements of the labor market. The aim of the paper is to examine whether the current legal framework of the Slovak Republic regulates statutory limits of determining and setting requirements for the performance of work by employees and in relation to whether it is "ready" for changes that will be reflected in the working area of employment relations. In the context of importance of training the workforce in the period to come, the author examines those legal aspects of the system of jobseekers’ and employees’ education that already cause problems in terms of applicability. In particular, the author focuses on the statutory obligation to provide education in the field of occupational health and safety, especially in the context of the adoption of recent legislation related to the pandemic.